Identifying Major Factors for Success and Failure of Conservation Programs in Europe - Nina Farwig; Philipp P. Sprenger; Bruno Baur; Katrin Böhning-Gaese; Angelika Brandt; Nico Eisenhauer; Götz Ellwanger; Axel Hochkirch; Alexandros A. Karamanlidis; Marion Mehring; Martin Pusch; Finn Rehling; et al. (Environmental Management, 2025)
In Europe, various conservation programs adopted to maintain or restore biodiversity have experienced differing levels of success. However, a synthesis about major factors for success of biodiversity-related conservation programs across ecosystems and national boundaries, such as incentives, subsidies, enforcement, participation, or spatial context, is missing. Using a balanced scorecard survey among experts, we analyzed and compared factors contributing to success or failure of three different conservation programs: two government programs (Natura 2000 and the ecological measures of the Water Framework Directive) and one conservation program of a non-governmental organization (NGO; Rewilding Europe), all focusing on habitat and species conservation. The experts perceived the NGO program as more successful in achieving biodiversity-related aims than governmental conservation legislation. Among the factors perceived to influence the success of biodiversity conservation, several stood out: Biodiversity-damaging subsidies, external economic interests competing with conservation goals or policies conflicting with biodiversity conservation were recognized as major factors for the lack of conservation success. Outreach to raise societal interest and awareness as well as stakeholder involvement were perceived as closely related to the success of programs. Our expert survey demonstrated that external factors from economy and policy often hinder success of conservation programs, while societal and environmental factors rather contribute to it. This study implies that conservation programs should be designed to be as inclusive as possible and provides a basis for developing a standardized methodology that explicitly considers indirect drivers from areas such as economy, policy and society.